Acrylamide Contents of Local Snacks in Singapore - Yeo, Michelle Ting Yun; Bi, Xinyan; Henry, Christiani Jeyakumar (Frontiers in Nutrition, 2021)
Acrylamide is a carcinogen that forms in foods processed at high temperatures. In this study, acrylamide contents of 30 local snacks commonly consumed by the three ethnic groups (Malay, Chinese, and Indian) in Singapore were analysed by using liquid chromatography-tandem mass spectrometry (LC-MS/MS). These snacks were chosen because they were consumed regularly by people of different classes and age groups in Singapore. Our results showed that the average content of acrylamide in Indian snacks (102.23 ng/g) was higher than those in Malay (75.14 ng/g) and Chinese snacks (70.78 ng/g). The high acrylamide levels in several snacks was probably due to the processing methods and the usage of acrylamide-inducing raw materials. Same snacks prepared by different manufacturers contained different levels of acrylamide, suggesting the possibility of acrylamide reduction in these snacks. This study provides an insight into the acrylamide levels of snacks commonly consumed by the three different ethnic groups in Singapore.